Identifying Appropriate Locations for the Accelerated Weathering of Limestone to Reduce CO2 Emissions - Julia S. Kirchner (MDPI AG, 2021)
The reduction in CO2 emissions is a major task for the coming decades. Accelerated weathering of limestone (AWL) can be used to capture CO2 from effluent gas streams and store it as bicarbonate in marine environments. We give an overview of the fundamental aspects of AWL, including associated CO2 emissions during the operation of AWL, characteristics of the accumulating bicarbonate-rich product water, and factors influencing the outgassing of CO2 from the ocean back into the atmosphere. Based on these aspects, we identify locations where AWL could be carried out favorably. The energy demand for AWL reduces the theoretical CO2 sequestration potential, for example, by only 5% in the case of a 100 km transport of limestone on roads. AWL-derived product water is characterized by high alkalinity but low pH values and, once in contact with the atmosphere, passive outgassing of CO2 from AWL-derived water occurs. This process is mainly driven by the difference between the fCO2 in the atmosphere and the oceanic surface layer, as well as the sea surface temperature at the discharge site. Promising sites for AWL may be in Florida or around the Mediterranean Sea, where outgassing could be prevented by injections into deep water layers.